12.8k views
0 votes
To find the constant vector C, we use the given initial condition v(0) = k, we also know that at t = 0, the general equation for v() i:s Comparing both equations for V(0) and solving for C, we have C = k. Substituting it back into the general equation, we have

V(t) = 4ti + 5tj + c = ______.

User Sneilan
by
4.9k points

1 Answer

4 votes

Answer:

4ti + 5tj + k

Explanation:

Initial condition V(0) = k

at t = 0

general equation for v(t )

V(0) = 0i + 0j + c = k

when we compare V(0) and solve for c , c = k

back to general equation

V(t) = 4ti + 5tj + c = 4ti + 5tj + k

User Vvnraman
by
5.7k points